2011
DOI: 10.1182/blood-2011-03-341933
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in plasma cell proliferation after initial therapy in newly diagnosed multiple myeloma measures treatment response and predicts improved survival

Abstract: Standard myeloma treatment response criteria are determined principally by changes in the monoclonal protein. Reduction in the size of the proliferative component of malignant plasma cells may be an additional metric of assessing response to therapy. We retrospectively analyzed 176 patients with newly diagnosed myeloma with a measurable plasma cell labeling index (PCLI) at diagnosis and repeat measurement 4 months after initiation of therapy. PCLI response was defined as a > 60% reduction. Baseline PCLI is an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…This underlines the need of useful biological and prognostic information's to develop rational and targeted therapies. The plasma cell labeling index was shown to be one of the most powerful risk factor in MM (10,11). However, this approach did not separate malignant MM cells from normal PC.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This underlines the need of useful biological and prognostic information's to develop rational and targeted therapies. The plasma cell labeling index was shown to be one of the most powerful risk factor in MM (10,11). However, this approach did not separate malignant MM cells from normal PC.…”
Section: Discussionmentioning
confidence: 96%
“…Proliferating PC, that is, the growing fraction of MM cells, have been evaluated by flow cytometry detection of newly synthesized DNA using techniques based on the uptake of tritiated thymidine or bromodeoxyuridine (BrdU) . The so‐called plasma cell labeling index (PCLI) based on propidium iodide incorporation has been shown to be a powerful and independent predictor of survival in MM as the assessment of Ki‐67 expressing cells in the malignant fraction . Although proliferation markers have been studied in MM, none of the current prognostic scores or staging systems, available to physicians nowadays, include these markers.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the heterogeneity of multiple myeloma [24], one single clinical index is unlikely to be able to differentiate between all tumour statuses, which supports the utility of different myeloma indices. We selected β 2 m and albumin for discriminant analysis, as these biochemical parameters are simple, easily available and inexpensive parameters that can be used as prognostic markers [25][26][27][28]. β2m is released into serum, with elevated levels in several lymphoproliferative disorders, including multiple myeloma.…”
Section: Discussionmentioning
confidence: 99%
“…Given that autologous stem cell transplantation (ASCT) is the most appropriate therapeutic choice for eligible patients, the role of tandem ASCT or alloSCT is still debated [16]. Other prognostic features related to the malignant clone are the proliferation index (PI) [17] and the plasmablastic morphology [18], both associated with frequent adverse cytogenetic lesions.…”
Section: Aggressive Clinical Presentationsmentioning
confidence: 99%
“…Apart from cytogenetic and molecular abnormalities, some clinical presentations observed at relapse, such as secondary plasma cell leukemia and extramedullary localizations, may benefit from certain specifically oriented strategies. Some authors have suggested adapting treatment in patients displaying a plasmablastic morphology and a high PI using anti-proliferative drugs, such as anthracyclines and inhibitors of aurora kinase [17,94].…”
Section: In the Long Run (After Tomorrow): A Combined Approach Includmentioning
confidence: 99%